PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP TINGKAT KONSERVATISME AKUNTANSI DI INDONESIA - Devi Ayu Novita Fadilla; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to examine the effect of corporate governance mechanism, such as board size, board independence, external auditor type, and ownership structure on accounting conservatisme in Indonesian companies. The data used in this research were obtained from company’s financial and non-financial statements and analyzed using multivariate regression techniques. All the Kompas 100 companies in January 2019 were considered, but excluding financial and utility firms. Other companies whose financial and/or governance data were not found were also excluded. Total sample in this research was 50 companies. The results of this research indicate that corporate governance is positively associated with accounting conservatism.